IMPLEMENTASI KOMUNIKASI PEMASARAN PADA PRODUK HASIL OLAHAN LIMBAH BOTOL PLASTIK DI KOTA MALANG - Rahayu, Yayuk Sri (Fakultas Ekonomi, UIN Maliki Malang, 2013)
Marketing communication has an important role in new product marketing process to inform dan promote the existing products. This research was focused and aimed to identify the implementation of marketing communication on recycle product from plastic bottles trashes at Malang. The research is descriptive qualitative and data was collected by quesionaire and observation. The result shows that producers of recycle product plastic bottles trashes have already implemented four marketing communication programs consist of advertising, sales promotion, publicity, dan personal selling. However, they have not implement direct marketing yet because lack of human resuorces.